Impact of Urbanization on Quality and Quantity of Groundwater in Nakhon-Nayok Province, Thailand - Juntakut, Pongpun; Jantakat, Yaowaret (International Journal of Building, Urban, Interior and Landscape Technology, 2019)
Groundwater has become an essential resource over the past few decades due to climate change, which highly increases the demand for using freshwater. The groundwater quality and quantity are then a significant criterion in matching water demand and supply. The objective of the study is to integrate the application of Geographic Information System (GIS) and Program R with the Water Quality Index (WQI) for the evaluation of groundwater quality and quantity in Nakhon-Nayok province, Thailand. The result of the study shows that the most community in western study area (Amphoe Ban Na) has WQI on average and below average levels. As a result, the urbanization can obviously impact on groundwater quality and quantity in the study area. Appropriate methods for monitoring and improving groundwater quality and quantity in affected areas should be suggested, especially in urban areas. In addition, this study indicates that the application of GIS and Program R with the WQI can be an effective tool and help more efficiently for groundwater management.